AJET in 2023: Reflections on educational technology, people, and bibliometrics - Corrin, Linda; Thompson, Kate; Lodge, Jason M. (Australasian Journal of Educational Technology, 2023)
In this editorial we reflect on the last three years of AJET achievements, challenges, and opportunities as we reach a time of transition in the lead editorial team. We also reflect on the key themes of 2023, especially the impact that the growing availability of generative artificial intelligence has had on research and practice in the tertiary education sector. We present our annual round up of bibliometrics, thank our hardworking editorial team, and acknowledge the contributions of those who are ending their service with AJET in 2023. In conclusion, we look ahead by outlining our goals for 2024 and discussing the themes and technologies that will be a focus for AJET in the new year.